Penguatan Diplomasi Ekonomi Tiongkok di ASEAN melalui ACFTA Upgrading Protocol - Calista Laurinne Nugraha (Insignia: Journal of International Relations, 2018)
The relationship between China and ASEAN through ASEAN - China Free Trade Area (ACFTA) has been going on for more than a decade. Unfortunately, during this period, it turned out that ACFTA received a lot of criticism. One of them is not significantly increasing trade – especially in ASEAN – as in the initial goal so that ACFTA was agreed to be reviewed in the ACFTA Upgrading Protocol asigned on November 21, 2015. However, in the renewal, China then insisted that ACFTA have a new cooperation agenda in the e-commerce sector. Even after that, multinational e-commerce companies from China such as Alibaba and Tencent began to expand into the ASEAN region, while ASEAN was not an e-commerce domain because the infrastructure was inadequate as in terms of internet speed and logistics network. This study aims to analyze why China added e-commerce cooperation in the ACFTA Upgrading Protocol. Using qualitative research methods and the concept of economic diplomacy, this research finds that the expansion of the ACFTA cooperation domain to the e-commerce sector is China's diplomatic strategy to strengthen its domination in ASEAN in order to achieve its vision as "strong internet power" (Wanglou Qiangguo). This vision was manifested in the Belt and Road Initiative (BRI) political agenda and the Internet Plus Strategy that was launched in 2013.